SISTEM INFORMASI E-PERPUSTAKAAN PADA SMK EKONOMIKA DEPOK - Hibatul Wafi (2023)
The library is the place most often visited by students to search book you want to read. With the use of digital technology as well as the internet, schools are SCHOOLS MEGAH VOCATIONAL ECONOMICS DEPOK implements a web-based library where all systems or processes are carried out online and in a system that can be accessed anywhere and anytime just. This research was conducted for the development of the Depokyang Economics Vocational School E-Library Website make it easier for students or teachers to find books or files used for learning. By using a Web Application in the form of a Web Server and Database Server, application This website is made through a structured and sequential process using the waterfall method, starting from the process analysis, website design, database design, program coding, this website is expected to provide convenience especially for students and school staff of DEPOK EKONOMIKA VOCATIONAL SCHOOL in finding books and files by online.